Implementation of the Internet of Things (IoT) in the nurse call system in hospitals (Nurse Call) - Erranaomi, Muhammad Brilian; Astuti, Femi Dwi (ReTII, 2024)
Hospitals are public facilities that are very much needed by the community. As technology advances, hospital facilities also develop with the presence of increasingly advanced technology. This study aims to develop and implement an Internet of Things (IoT)-based nurse calling system in hospitals using Message Queuing Telemetry Transport (MQTT) technology and the ESP8266 microcontroller. IoT is a concept that allows various devices to connect and communicate with each other via the internet, thus facilitating real-time data exchange without human interaction. This system allows patients to call nurses in real-time through devices connected to a Wi-Fi network. Messages sent from devices in each patient’s room are forwarded to the MQTT server, which then sends notifications to the nurse application. Testing was carried out to measure the latency, reliability, and power consumption of the system. From the results of 100 experiments, the average latency obtained varied depending on the distance between the ESP8266 device and the Access Point, with the lowest average latency of 26.72 ms at a distance of 15 meters, and the maximum latency reaching 2897 ms at a distance of 20 meters. The system demonstrated 100% reliability, with no packet loss during testing. In terms of power efficiency, the device consumes only 0.35 watts, making it energy efficient and suitable for long-term implementation in hospital environments. With acceptable latency and high reliability, the system is expected to improve nursesâ€™ response time to patients, as well as provide an efficient and reliable communication solution in hospitals.